2015
DOI: 10.1136/jech-2015-205959
|View full text |Cite
|
Sign up to set email alerts
|

Ebola, jobs and economic activity in Liberia

Abstract: BackgroundThe 2014 Ebola virus disease (EVD) outbreak in the neighbouring West African countries of Guinea, Liberia and Sierra Leone represents the most significant setback to the region's development in over a decade. This study provides evidence on the extent to which economic activity declined and jobs disappeared in Liberia during the outbreak.MethodsTo estimate how the level of activity and number of jobs in a given set of firms changed during the outbreak, we use a unique panel data set of registered fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 9 publications
4
39
0
Order By: Relevance
“…This suggests that the effects of the EVD epidemic were not limited to the communities where EVD occurred, but that the EVD crisis affected communities throughout the country. These results are in line with the findings of Bowles et al (2016) [ 63 ] who reported that during the EVD epidemic, there was a remarkable decline in economic activities across Liberia, but that in most cases, there was little association between the decline in economic activities and the number of Ebola cases. Thus, post-epidemic rehabilitation measures should not only be limited to communities directly affected by EVD, but should also target those indirectly affected by the epidemic.…”
Section: Resultssupporting
confidence: 92%
“…This suggests that the effects of the EVD epidemic were not limited to the communities where EVD occurred, but that the EVD crisis affected communities throughout the country. These results are in line with the findings of Bowles et al (2016) [ 63 ] who reported that during the EVD epidemic, there was a remarkable decline in economic activities across Liberia, but that in most cases, there was little association between the decline in economic activities and the number of Ebola cases. Thus, post-epidemic rehabilitation measures should not only be limited to communities directly affected by EVD, but should also target those indirectly affected by the epidemic.…”
Section: Resultssupporting
confidence: 92%
“…Most researches about public health emergencies have focused on changes in overall consumption trends. By reviewing public health emergencies in the past 20 years, some major research perspectives were found, such as consumption trends, consumption behavior, changes in consumer decision-making and consumer psychology and so on [21,22,23,24]. These researches con rm that the pandemic reduces economic activity and employment and inhibits consumption, which consists with our ndings on the impact of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 63%
“…For the pressure shown in Q3, rms were facing employment and settlement costs. In addition, 22.9% of rms encountered cancellation of orders from domestic customers. Many rms showed that the market expansion was also affected, due to the impossibility of site visiting and face to face interviews to customers.…”
Section: The Impact Of the Pandemic On Rmsmentioning
confidence: 99%
“…Outbreak control activities also led to the closure of schools, markets and hospitals, and some countries even closed borders for fear of mass transmission. Through outbreak control activities and spurred by fears of transmission, the EVD outbreak had a significant impact on the economy of the region, reducing agriculture and fishing, mainstays of the communities and severely curtailing business and trade activities 11. Further public health deterioration operated through economic pathways, increasing poverty and food insecurity 12…”
mentioning
confidence: 99%